ARTIFICIAL INTELLIGENCE AS AN ENABLER OF THE HALAL BUSINESS INDUSTRY 4.0: OPPORTUNITIES, CHALLENGES, AND ETHICAL IMPLICATIONS - Sanawi; Itang; Hadi Peristiwo; Ahlam Tri Anugrah (Universitas Mathla’ul Anwar Banten, 2026)
This study discusses the role of Artificial Intelligence (AI) as an enabler in the development of Halal Industry 4.0, with a focus on identifying opportunities, challenges, and accompanying ethical implications. The transformation towards Halal Industry 4.0 is characterized by digitalization and the integration of intelligent technologies that enable efficiency, transparency, and increased competitiveness of halal products and services in the global market. AI plays a strategic role in accelerating the halal certification process, supporting real-time halal supply chain management, and facilitating product innovation oriented to the needs of global Muslim consumers. Furthermore, the integration of AI in the halal industry also raises significant ethical implications, including issues of data privacy, algorithmic fairness, potential technological bias, and strengthening authority in determining halal legitimacy that must still refer to the principles of maqasid al-shariah. Thus, the adoption of AI in Halal Industry 4.0 requires a holistic approach that emphasizes not only technical efficiency but also ensures compliance with ethical, spiritual, and social values. This study uses a qualitative approach with a descriptive analytical design to examine the role of Artificial Intelligence (AI) as an enabler in the development of Halal Industry 4.0, focusing on opportunities, challenges, and ethical implications. The results indicate that the success of AI as a catalyst for global halal transformation depends on the ability of all stakeholders government, academics, industry players, and religious authorities to maximize opportunities, address challenges, and wisely manage ethical implications. With this framework, AI can be a crucial instrument in building an inclusive, globally competitive halal industry that remains rooted in sharia principles and sustainability.